2019
DOI: 10.1002/fuce.201800135
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Effect on the PEMFC Performance

Abstract: A three‐dimensional and two‐phase computational fluid dynamics (CFD) model for a single serpentine channel polymer electrolyte membrane fuel cell (PEMFC) based on ANSYS FLUENT fsimulation software is used to investigate the pressure effects on the PEMFC performance. The model is validated by a series of experiments and the numerical data fit well with the experiment results. The PEMFC performance is improved as the increase in back pressure. The simulation results revealed an important mechanism between pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The performance difference gradually decreases with elevated pressure, while the performance improvement is basically the same with the same temperature rise. This is because the ratio of pressure increase to the operating pressure is reduced and the impact on cell performance will be diminished 47 . As thus, polarization curve fitting is based on the operating conditions, which provides a basis for BOP selection and control strategy development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance difference gradually decreases with elevated pressure, while the performance improvement is basically the same with the same temperature rise. This is because the ratio of pressure increase to the operating pressure is reduced and the impact on cell performance will be diminished 47 . As thus, polarization curve fitting is based on the operating conditions, which provides a basis for BOP selection and control strategy development.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the ratio of pressure increase to the operating pressure is reduced and the impact on cell performance will be diminished. 47 As thus, polarization curve fitting is based on the operating conditions, which provides a basis for BOP selection and control strategy development.…”
Section: Polarization Curve Under Different Operation Conditionmentioning
confidence: 99%
“…[4][5][6] Therefore, it is necessary to improve MSR technology in order to reduce heating and steam requirements and achieve a cost-efficient H2 manufacture. In this sense, the capability to operate fuel cells at ambient pressure, 7 and the development of hydrogenselective membrane reactors, [8][9][10] represent an opportunity to increase the thermodynamically limited conversion imposed by the endothermicity of the MSR reaction, 11 allowing both lower operating temperatures (500-600 °C) and lower steam-to-methane ratios, while maintaining good H2 yield. Commercial catalysts in industrial reforming units, typically consisting of nickel on magnesium or aluminum oxides supports, are designed to withstand high-temperature operation without losing strength, and thus prioritize stability and thermal resistance over surface area.…”
Section: Introductionmentioning
confidence: 99%
“…Rohendi et al [12] confirmed that when the performance of the membrane electrode assembly (MEA) was degraded after an operating time of 100 h followed by the application of backpressure, the cell conductivity was improved, and the open circuit voltage (OCV) was maintained compared with that under ambient conditions. Lu et al [13] applied a 3D computational fluid dynamics (CFD) model to inspect the effect of pressure on the PEMFC performance and found that high backpressure leads to high relative humidity in the cathode channel, which contributes to high membrane water content.…”
Section: Introductionmentioning
confidence: 99%